Trend growth and learning about monetary policy rules in a two-block world economy - Eric Schaling; Mewael F. Tesfaselassie (Kiel Institute for the World Economy (IfW), 2013)
Available evidence supports the view that growth is faster in more open economies. In order to analyze the implications of openness and growth on determinacy and learnability of worldwide rational expectations equilibria we develop a two-country New Keynesian model with growth. We analyze these issues for contemporaneous data and expectations-based monetary policy rules. Our results highlight how growth matters for the overall effect of opening an economy to more trade, as we find that (i) under the contemporaneous data policy rule the conditions for determinacy and learnability become more stringent on account of openness but less stringent on account of growth, so that growth weakens the effect of openness, (ii) under the expectations-based policy rule the conditions for determinacy and learnability also become more stringent on account of openness while on account growth the conditions for determinacy become more stringent (thus reinforcing the effect of openness) but those for learnability become less stringent (thus weakening the effect of openness). As in Bullard and Schaling (2009) the elasticity of intertemporal substitution is key to our result but within a framework that is consistent with long-run labor supply and balanced growth facts.
Keywords: E58; E61; F31; F41; 330; trend growth; open economy; monetary policy rules; determinacy; learning